Pengaruh Kualitas Pelayanan, Kualitas Produk dan Harga terhadap Loyalitas Pelanggan: Studi Kasus di Olshop Patricia Akesesoris (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of service quality, product quality, and price on customer loyalty at the online shop Patricia Aksesoris. This research is motivated by the increasingly fierce competition in the e-commerce business, which requires businesses to not only attract new customers but also retain existing ones by increasing loyalty. Customer loyalty is a crucial factor because it directly impacts business sustainability and competitive advantage. This study used a quantitative approach with a survey method, distributing questionnaires to customers who had previously purchased from Patricia Aksesoris. The sampling technique used purposive sampling. The collected data were analyzed using multiple linear regression to determine the effect of each independent variable on customer loyalty. The results indicate that service quality, product quality, and price, both partially and simultaneously, have a positive and significant effect on customer loyalty. These findings indicate that responsive and friendly service, products that meet customer expectations, and competitive pricing commensurate with product quality can increase customer loyalty. This research is expected to provide practical contributions to online shop owners in formulating marketing strategies oriented towards customer satisfaction and loyalty.